Nutrition and exercise interventions on skeletal muscle physiology, injury and recovery: From mechanisms to therapy - Hirabara, S. M.; Marzuca-Nassr, G. N.; Cury-Boaventura, M. F. (Nutrients, 2024)
Interventional strategies involving nutrition and physical exercise have been widely proposed to positively modulate skeletal muscle function, in both physiological and pathological states, such as obesity, T2DM, inflammatory diseases, cardiovascular diseases, aging, and sarcopenia [1,2,3]. In this sense, it has been observed that various nutrients or dietary bioactive compounds positively modulate different biological processes, such as metabolism, inflammation, redox balance, mitochondrial function, and gene expression. Several physical exercise protocols have also been proposed to maintain, increase, or recover skeletal muscle function [4,5,6]. Research groups are focusing potential molecular targets to direct further studies to treat and/or prevent skeletal muscle disorders.